Developing Life Skills Through Extracurricular Sports in The Framework of Positive Youth Development (PYD) : Systematic Literature Review - Adi Maulana Mahmud; Yudi Hendrayana; Tite Juliantine (Universitas Negeri Semarang, 2024)
How PYD is believed to provide benefits to youth development, one of which is that the PYD program provides resources that promote PYD to foster or stimulate individual contextual relationships that are contrary to criminal, violent, or disruptive attitudes and behaviors. Of the various PYD programs, one of the programs is the development of Life Skills for young people. Sports are one of the means that have a high potential for developing life skills. The purpose of this study is to find out whether extracurricular sports programs can be used to improve life skills and to find out how to carry out extracurricular sports programs to develop life skills. This study uses a systematic literature review method using: (1) identification of journals to be used (2) selection, namely the assessment of the quality of research reports, (3) in the form of quantification of the results of each review to be combined, and (4) analysis, namely the combination and reporting of results. The findings show how extracurricular sports can be used to develop life skills in the context of positive youth development. The development of extracurricular sports can be done in a structured and unstructured manner. The study shows how structured life skills development is better than unstructured ones.